Teaching phonological awareness: a comparative analysis according to the development of collaboration between teachers and Speech-Language Pathology - González-Fernández, Daniela; Flores-González, Felipe; Amaya-Medina, Durley Ruth; Iturra-Osorio , Daniela (Revista de Investigación en Logopedia, 2024)
Phonological awareness (PA) is a key skill in learning to read. From an inclusive scenario, collaboration between teachers and speech therapists is essential for the development of learning, especially for children with language difficulties. The purpose of this research was to compare sociodemographic characteristics and the PA intervention in the classroom between speech therapists who present different levels of development of collaborative work.A questionnaire was applied to 112 speech therapists, active in the educational field. Through a cluster analysis, the sample was divided into two groups, based on the level of development of collaborative work. Subsequently, sociodemographic characteristics and aspects of the intervention in teaching PA, in the classroom, were compared.The results reveal that speech therapists can be classified into two groups, according to their level of collaboration (low collaboration=29; high collaboration=83). Although no significant differences were found in sociodemographic terms, notable variations were identified in aspects of the speech therapy intervention, such as the percentage that considers the phonemic level (p=.0017), the focus placed on the approach during the first primary school year (p=.06), and the time spent preparing materials (p=.033). It is concluded that the collaborative approach to PA favors interventions that are aligned with the reported evidence. These results may be useful for teachers and speech therapists to consider collaborative practices development during PA teaching.
Keywords: classroom environment; collaborative work; phonological awareness